2016
DOI: 10.29252/ijrm.14.7.7
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA-E gene polymorphism and unexplained recurrent spontaneous abortion (RSA) in Iranian women

Abstract: Background:Human leukocyte antigen-E (HLA-E)is a non-classical major histocompatibility complex (MHC) class I antigens which expressed on extra villous cytotrophoblast, which interacts with NKG2A, is an inhibitory receptor on natural killer (NK) cells and leading to down regulation of immune response in the maternal-fetal interface and provides maternal immune tolerance of the fetus.Objective:This study was designated to investigate the gene frequencies of E0101 and E0103 in HLA-E gene in Iranian women with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The mean expression of NK cells in the trophoblast on IUFD was higher compared to normal pregnancy. The results of this study were in line with the research conducted by Fotoohi in 2016 that obtained lower HLA-E in recurrent spontaneous abortion including IUFD than normal pregnancy because HLA-E is an antigen that interact with NKG2A which is a receptor inhibitor of NK cells that help the fetus to face the response of maternal immunity, so when HLA-E deficiency occurs, the fetus is more vulnerable to NK cells attack that will cause IUFD (Fotoohi et al 2016).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The mean expression of NK cells in the trophoblast on IUFD was higher compared to normal pregnancy. The results of this study were in line with the research conducted by Fotoohi in 2016 that obtained lower HLA-E in recurrent spontaneous abortion including IUFD than normal pregnancy because HLA-E is an antigen that interact with NKG2A which is a receptor inhibitor of NK cells that help the fetus to face the response of maternal immunity, so when HLA-E deficiency occurs, the fetus is more vulnerable to NK cells attack that will cause IUFD (Fotoohi et al 2016).…”
Section: Discussionsupporting
confidence: 78%
“…HLA-E can protect trophoblast from maternal-fetal immune intolerance and allow the trophoblast cells to invade the uterus. HLA-E plays an important role in immune tolerance during pregnancy (Fotoohi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to HLA-G polymorphisms, an association between HLA-E polymorphisms and RSAs has been observed. The HLA-E 0101 allele, compared with the HLA-E 0103 allele, was significantly higher in women suffering from RSAs [127].…”
Section: Interaction Of Hla-e To -G With Receptor Families Of Immumentioning
confidence: 99%
“…It has been observed that there was higher frequency of HLA‐E 0101 polymorphism among a sample of Iranian RSA cases compared with controls, whereas HLA‐E 0103 was more frequent among controls. Moreover, the HLA‐E0101/0103 heterozygous genotype was correlated with fetus maintenance among Iranians (Fotoohi, Ghasemi, Mirghanizadeh, Vakili, & Samadi, ).…”
Section: Human Leukocyte Antigensmentioning
confidence: 99%